DEPRECIATION ACCOUNTING METHODS FOR PUBLIC UTILITIES. - Nash, L. R. (The Accounting Review, 1930)
Abstract This paper deals with only that part of the broad subject of depreciation which relates to the method of accumulating adequate reserves through which to retire property that ceases to be useful. The discussion is further restricted to the field of public utilities as they exist in the United States because of the special conditions under which their operations are conducted. Nearly all public utilities are subject to regulation by governmental bodies, usually state commissions. Theoretically, their operations are monopolistic, and one of the primary functions of regulation is to fix rates which will yield a return to investors consistent with that which they could obtain from investments in other industries with similar risks. Refinement in such accounting is in many respects more important than in other industries operating on a competitive basis with prices determined by the law of supply and demand. The early years of public utility history were devoted to pioneering and development work, with comparatively little attention to accounting.